РЕФОРМИРОВАНИЕ УЧЕБНЫХ ПРОГРАММ И ВОПРОСЫ ТЕОРИИ И ПРАКТИКИ ПЕРЕВОДА - Рзаева, Р.К.; Ешимбетова, Н. (SCIENCE and SOCIETY, 2017)
The article is devoted to the issues of reforming curriculums in foreign languages, and theory and practice of translation. There have been analyzed the results of PRESETT curriculum in teaching English of the students of pedagogical institute, and its role in the development of habits and skills in translation. The author of the article also describes the work in translation being done by the members of the scientific circle «Young translator» and teachers that is considered to be the contribution into the development of theory and practice of translation in the republic.
Keywords: reformation; curriculum; means of communication; methods of teaching; international standards; innovational methods of teaching; types of language activities; media-technologies; theory and practice of translation; literary-artistic translation